Simulation Analysis and Forecasting of COVID-19 Spreading in Malaysia - SULAIMAN, NUR FATEHAH; IBRAHIM, NORZURIA (Enhanced Knowledge in Sciences and Technology, 2023)
Coronavirus disease 2019 (COVID-19) can be interpreted as a disease caused by a novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; formerly known as 2019-nCoV). The deaths caused by coronavirus continue to increase the mortality rate by about 5% due to the wide spread of the disease geographically[5]. Based on Kermack and McKendrick (1927), their plague model, is considered one ofthr earlierst model for a system of four ordinary different equations. This study aimed to develope and simulate the ’susceptible-exposed-infected-recovered (SEIR)’ model of covid-19 using Python. Python was used to analyse the spread of the pandemic in Malaysia. The SEIR model simulation model was developed over a year for analyze. Next, this research continued by forecasting the infected and recovery of Covid-19 in Malaysia using Excel. The results showed the graph of infection and recovery from 25 November 2022 to 31 March 2023 is reduced and close to zero. To obtain more accurate predictive values, research can continue to predict infection and Covid 19 recovery using different software such as ARIMA